Improving Nutrition : Issues in Management and Capacity Development - Heaver, Richard (World Bank, Washington, DC, 2013)
The World Bank has not yet defined the main issues in management and capacity development in nutrition, nor has it developed methodologies for governments and project staff to identify and deal with these issues and systematically improve capacity. This issues paper is intended as a starting-point for developing the Bank's professional capacity in nutrition management and capacity development. It discusses a dozen sets of issues related to the design and implementation of community nutrition programs: community empowerment and decentralization; staffing and job design; supervision, training and referral; program monitoring and evaluation; sectoral capacity analysis and strategy development; building understanding, commitment and behavioral change; managing the nutrition sector; managing nutrition program support organizations; tools for institutional analysis and capacity development; building technical assistance capacity; improving donor cooperation; and improving coordination across sectors. As a follow-up, it suggests priorities for a work program in management and capacity development in nutrition, including: preparing case studies of successful nutrition programs; preparing best-practice nutrition projects with strong emphasis on capacity development; creating groups to focus on management and capacity development in key institutions dealing with nutrition; creating networks between nutrition institutions to share experience in this area.